What do People have to do with Sport? Folklore/Ethnology in the Kinesiology Classroom - Robidoux, Michael (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
This article discusses the challenges and strengths faced by a Folklorist teaching in a Kinesiology Department. It specifically focuses on a fieldwork assignment in a History of Sport class, where students were required to collect oral histories of sport from within their communities. The author discusses how, as a professor, he legitimized this exercise to the students, the students’ response to it, and the outcome of the research exercise. He intends to illustrate how folklore principles in the classroom achieve a greater understanding of the cultural value of sport, but also generate greater interest in the subject matter at hand.